1986
DOI: 10.3382/ps.0650325
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of α-Amylase Activity in Selected Broiler Tissues

Abstract: In an examination of broiler alpha-amylase, significant variation in the serum enzyme activity level was noted, adult levels were lower than those of young chicks. Analysis of alpha-amylase activity in various body fluids and tissues of 11-day and 7-week-old broilers indicated that the liver cannot be considered a source of alpha-amylase, although there was activity in both liver tissue and bile of 10 units/g wet weight and 35 units/100 ml, respectively. Fluid from the oral cavity had low levels of alpha-amyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…It contains complex carbohydrates and acts to lubricate the mucosal membranes, facilitates transport of nutrients across mucosal membranes and exerts a chemical/mechanical defense of the mucosa against pathogens. There is also evidence for the starch digesting enzyme, alpha amylase, in the oral cavity coming from the salivary glands (Jerrett and Goodge, 1973;Rodeheaver and Wyatt, 1986). The amylase may be breaking down starch during transit and storage of ingesta in the crop and proventiculus.…”
Section: Mouthmentioning
confidence: 98%
“…It contains complex carbohydrates and acts to lubricate the mucosal membranes, facilitates transport of nutrients across mucosal membranes and exerts a chemical/mechanical defense of the mucosa against pathogens. There is also evidence for the starch digesting enzyme, alpha amylase, in the oral cavity coming from the salivary glands (Jerrett and Goodge, 1973;Rodeheaver and Wyatt, 1986). The amylase may be breaking down starch during transit and storage of ingesta in the crop and proventiculus.…”
Section: Mouthmentioning
confidence: 98%
“…These results are in agreement with those of other researchers (Kosa et al, 2004, Sabatakou et al, 2006, Debray et al, 2001), who described a significantly increase of α-amylase activity according to the progress of age up to 35-day old rabbits, at the level of intestine. (B) On the con trary, the α-amylase activity in 35-day old ERE rabbits showed that the α-amylase activity and concentration in both blood plasma and intestinal epithelium were significantly (a=0.05) decreased (Philips andFuller, 1983, Rodeheaves andWyatt, 1986). …”
Section: Discussionmentioning
confidence: 99%
“…Amylase is found in the liver, bile, saliva, and pancreas, with the pancreas being the major source. Amylase activity, therefore, can be used to diagnose pancreatic function [42]. γglutamyl transpeptidase is a cell membrane enzyme related to glutathione metabolism and amino acid absorption in the glomerulus and small intestine [43].…”
Section: Trialmentioning
confidence: 99%